Use of adjuvant ISA VG 71 to produce neutralizing egg yolk antibodies against bothropic venom - Leiva, Carlos Leónidas (2023)
The use of egg yolk antibodies—IgY technology—represents an alternative to the production of mammalian immunoglobulins and has several advantages regarding animal welfare and lower costs of production. The use of adjuvants to achieve the hyperimmunization of laying hens plays a key role in the success of the production of high levels of the antibodies. In the present work, two different adjuvant systems (Freund’s adjuvants and MontanideTM ISA 71 VG) were compared to produce IgY anti-Bothrops alternatus. For the first immunization, formalin-inactivated Salmonella was added to MontanideTM ISA 71 VG to emulate Freund’s complete adjuvant which includes a mycobacteria antigen. After eight immunizations, IgY produced by using either adjuvant was able to neutralize the lethal activity of the venom in a mouse model, but differences were found regarding the recognition of components of the venom between the two adjuvants tested. Overall, MontanideTM adjuvant used in this work could be a good alternative choice to produce antibodies capable of neutralizing the lethality of complex antigens. This adjuvant is commercially available and used in the formulation of several poultry vaccines and could be used for the IgY technology instead of traditional immunomodulators such as Freund’s adjuvants.